A practical method to remove perfluorooctanoic acid from aqueous media using layer double hydride system a prospect for environmental remediation - Ahmed, Ammara (Environmental technology, 2022)
Perfluorooctanoic acid (PFOA) is an organic compound that is persistent and very toxic to living organisms and the environment. In this study, two kinds of Mg-Al-layered double hydroxides (namely LDH-1 and 2) were synthesized using hydrothermal and dry grinding methods and used to adsorb PFOA from aqueous solution. The kinetic study revealed that a pseudo-2nd order model was the best method for describing the kinetics of sorption, which could emphasize the chemical interaction between PFOAs and LDHs. Among the models tested, the Freundlich model was the best fit for the sorption isotherms. The removal rates of PFOA adsorption by LDH-1 and LDH-2 were 90% and 98.9%, respectively, in the lowest time compared with similar past studies using different adsorbents. The currently synthesized LDHs showed the least equilibrium time, without thermal treatment and the need for activation. The research bears prospects for removing PFOA from aqueous media, thereby demonstrating the potential of employing synthesized LDHs in a fixed-bed filter for the environmental remediation of PFOA-contaminated wastewater bodies